Integração de demanda e suprimentos: um estudo de caso sobre o papel da tecnologia na integração interfuncional em uma empresa multinacional do agronegócio - Lima, Francisco Arnaldo Ferraz (2020)
Internal integration brings about optimizating and restructuring activities for greater collaboration and synergy in task execution and effective information sharing. Integration reduces duplicate tasks, that do not add value to the process, and provides information sharing and greater cross-functional alignment, improving business efficiency and performance. The use of technology in the integration processes can improve information flow and accessibility, reduce response times, and streamline the process. Despite of the massive existence of literature on supply chain integration, more specifically about cross-functional integration, the discussion about the technology influence on cross-functional integration is scarce, mainly regarding the integration between functions from demand and supply sides and its impact on processes. Therefore, this work aims to analyze the cross-functional integration between supply and demand in inbound processes in an agribusiness company focused on the use of technologies from Industry 4.0. A case study was conducted in a global agribusiness company that experienced a process of restructuring activities with the implementation of a shared service center. Fifteen in-depth interviews were conducted with employees from the demand and supply areas. The analysis involved description of cross-functional integration processes from the areas of demand and supply, the identification of technologies from industry 4.0 present in the activities of those areas and their role in the integration process. The analysis of the integration of demand and supply areas through the technologies employed allowed us to observe the mediating role of the technology in the cross-functional integration, the presence of new integration factors and their impact on the process performance. The results allowed to develop a framework that describes the relationship between technology and integration factors and their impacts.